2020
DOI: 10.1182/blood.2019003793
|View full text |Cite
|
Sign up to set email alerts
|

IL10RA Modulates Crizotinib Sensitivity in NPM1-ALK-positive Anaplastic Large Cell Lymphoma

Abstract: Anaplastic Large Cell Lymphoma (ALCL) is a T-cell malignancy predominantly driven by a hyperactive Anaplastic Lymphoma Kinase (ALK) fusion protein. ALK inhibitors such as crizotinib provide alternatives to standard chemotherapy with reduced toxicity and side effects. Children with lymphomas driven by NPM1-ALK fusion proteins achieved an objective response rate to ALK inhibition therapy of 54-90% in clinical trials. However, a subset of patients progress within the first 3 months of treatment. The mechanism for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 82 publications
0
48
0
Order By: Relevance
“…The IL-10/IL-10RA signaling pathway can reverse the effects of crizotinib-inhibition on STAT3 activity. Activated STAT3 further binds to the transcriptional start sites of IL-10/IL-10RA/IL-10RB in ALCL cells [ 47 ]. Trastuzumab treatment rendered resistance to itself, facilitated epithelial-to-mesenchymal transition and enhanced metastatic potential in gastric cancer cells through an IL6/STAT3/Jagged-1/Notch positive feedback loop [ 48 ].…”
Section: Feedback Loop Leading To Stat3 Activationmentioning
confidence: 99%
“…The IL-10/IL-10RA signaling pathway can reverse the effects of crizotinib-inhibition on STAT3 activity. Activated STAT3 further binds to the transcriptional start sites of IL-10/IL-10RA/IL-10RB in ALCL cells [ 47 ]. Trastuzumab treatment rendered resistance to itself, facilitated epithelial-to-mesenchymal transition and enhanced metastatic potential in gastric cancer cells through an IL6/STAT3/Jagged-1/Notch positive feedback loop [ 48 ].…”
Section: Feedback Loop Leading To Stat3 Activationmentioning
confidence: 99%
“…9,29,30 In clinical practice, many refractory NPM1-ALKþ ALCL patients are treated with crizotinib as an alternative to standard chemotherapy. 42 Recently, the FDA also approved crizotinib in children and young adults with relapsed or refractory ALKþ ALCL. NPM1-ALK fusion-driven pediatric lymphomas showed an objective response rate to crizotinib therapy while a subset of patients progressed in the first 120 days of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of IL10RA was indicated to be responsible for crizotinib resistance in NPM1-ALK-driven ALCL cells. 42 A phase I clinical trial result showed that ceritinib had marked antitumor activity on crizotinib (a first-generation ALK inhibitor)-resistant EML4-ALKþ NSCLC tumors, including those with ALK mutations at amino acid residues at position 1196, 1269, 1171, or 1206. The preclinical data from crizotinib-resistant NPM1-ALKþ ALCL clones shared some common ALK mutations that are found in NSCLC (amino acid residues at 1196 and 1171).…”
Section: Discussionmentioning
confidence: 99%
“…Only IL-6 showed an independent prognostic value in multivariate analyses [ 65 ]. Aberrant upregulation of interleukin 10 receptor subunit alpha (IL10RA) is observed in both ALK+ and ALK- ALCL and triggers STAT3 phosphorylation independently of NPM-ALK1 in ALK+ ALCL [ 66 ].…”
Section: Cytokines In Alclsmentioning
confidence: 99%
“…Resistance to ALK inhibition may be acquired by the emergence of specific ALK mutations that may be counteracted by new-generation inhibitors such as alectinib or ceritinib [ 105 ]. IL-10 autocrine synthesis and aberrant upregulation of the IL-10 receptor subunit also bypass NPM-ALK inhibition and contribute to single-ALK inhibitor resistance [ 66 ].…”
Section: Therapy Of Alclsmentioning
confidence: 99%